2016
DOI: 10.2147/jaa.s85624
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-disordered breathing in children with asthma: a systematic review on the impact of treatment

Abstract: BackgroundThe objective was to perform a systematic review in order to describe the relationship between asthma and sleep-disordered breathing (SDB) in children, especially regarding the impact of treatment and management.MethodsWe performed an electronic search in MEDLINE, EMBASE, and LILACS database. Study inclusion criteria were the following: 1) studies that examined the relationship between asthma/wheezing and SDB/obstructive sleep apnea (OSA); and 2) studies conducted in children <18 years of age. Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 56 publications
(172 reference statements)
0
18
0
Order By: Relevance
“…The link among asthma and sleep-related breathing disorder (SRBD) is bidirectional due to common risk contributors that, finally, induce airway inflammation ( 7 , 8 ). SRBD in children with asthma may lead to difficult-to-control asthma.…”
Section: Introductionmentioning
confidence: 99%
“…The link among asthma and sleep-related breathing disorder (SRBD) is bidirectional due to common risk contributors that, finally, induce airway inflammation ( 7 , 8 ). SRBD in children with asthma may lead to difficult-to-control asthma.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 However, until now, the prevalence of OSA in patients with asthma, especially in children with asthma, has not been clearly demonstrated. In a recent systematic review, Sánchez et al 7 showed that children with asthma had a significant and higher risk of OSA than subjects without OSA and that both diseases shared some similar symptoms (overlap) during sleep, making the diagnosis of each more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…A bidirectional relationship appears to exist between various health concerns and sleep quality. 1,11,12,27,28 A strong correlation between hypertension, cardiovascular disease, and stroke compared with the quality and quantity of sleep has been consistently shown in literature. 29 Children who have undiagnosed and untreated sleep disruptions and/or sleep disorders are also at increased risk for hypertension.…”
Section: Systemic Health Concerns Related To Poor Sleepmentioning
confidence: 83%
“…34 Sleep-disordered breathing and asthma have been correlated, as both are inflammatory disorders of the upper and lower airways and can contribute to respective worsening of each condition and possibly lead to OSA. 27 To make matters more complicated, many of the medications used to treat sleep-related medical conditions contribute to poor sleep due to the type of receptor antagonist effect in the brain. 2 According to the National Sleep Foundation, medications taken to treat nasal congestion, hypertension, heart disease, thyroid disorders, birth control, breathing issues, and cognitive health concerns can contribute to difficulty with falling and/or staying asleep.…”
Section: Systemic Health Concerns Related To Poor Sleepmentioning
confidence: 99%
See 1 more Smart Citation